Penerapan Metode Pewarnaan Graf Untuk Penjadwalan Mata Kuliah - Amelia Yusnita; Hanifah Ekawati; Nila Ratna Wati (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Scheduling courses is a routine agenda every semester carried out by the study program, in the manufacturing process it often experiences difficulties such as frequent clashes between courses, lecturers and other times in one period of the lecture schedule. The graph coloring method used is a simple row coloring algorithm on the side. This algorithm can be used in scheduling so that there is no overlap between courses, lecturers, room and time. The system design tool used is a flowchart. The results of this study are in the form of applications that are made automatically without any conflicting schedules. Users can enter the initial scheduling data according to their needs, then the application will follow scheduling using a simple line coloring algorithm on the side, and the output results will display the scheduling results. testing using black box, this test will test in detail the plus button and process button, the expected result is a success